2014
DOI: 10.1149/2.0361414jes
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Kinetics of Electroless Cu Deposition on Ruthenium Using Glyoxylic Acid as a Reducing Agent

Abstract: Glyoxylic acid is seen as a promising candidate to replace formaldehyde as reducing agent in electroless Cu baths. For deposition on ruthenium, the anodic reaction of glyoxylic acid has been evaluated and compared to formaldehyde using linear sweep voltammetry. Significant differences were observed for the deposition of copper on ruthenium. First of all, a faster nucleation was inferred from open-circuit potential measurements, which is beneficial as it reduces the total process time. Secondary, we found 2,2 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…22 In addition, in our previous study, it was clarified that glyoxylic acid can show anodic oxidation on both Cu and Ru. 26 Figure 1 shows linear sweep voltammograms of glyoxylic acid and formaldehyde for a 30 nm Co liner. For the case of formaldehyde, anodic oxidation was absent in the range from −0.65 to −0.45 V, which is the potential range in which the reducing agent should be active to lead to reduction of the Cu-EDTA complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In addition, in our previous study, it was clarified that glyoxylic acid can show anodic oxidation on both Cu and Ru. 26 Figure 1 shows linear sweep voltammograms of glyoxylic acid and formaldehyde for a 30 nm Co liner. For the case of formaldehyde, anodic oxidation was absent in the range from −0.65 to −0.45 V, which is the potential range in which the reducing agent should be active to lead to reduction of the Cu-EDTA complex.…”
Section: Resultsmentioning
confidence: 99%
“…In recent work, we found that the glyoxylic acid oxidation on Ru is impacted by dissolved oxygen. 26 Therefore, removing the oxygen by N 2 bubbling and/or deposition in an inert atmosphere could increase the reactivity of the reducing agent for the ELD process. 29 Cathodic reaction of Cu complex on Co.-For a self-catalyst electroless process, both reducing agent and complexed Cu ions should be present.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the driving force of the ELD reaction is the oxidation of the reducing agent at the surface, which can be strongly impacted if the surface has native oxide or other foreign contamination. In this work, glyoxylic acid is used as a reducing agent [2][3][4][5]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the nucleation of Cu deposition can take place without a Ru surface activation step. However, such an in-situ cleaning process likely causes insufficient cleaning, which could result in an increased Cu/Ru interfacial impurity levels [4]. Furthermore, the increase of the temperature shortens the bath life time and therefore increases the total process cost.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation